IMPORTANT ISSUES OF COOPERATION WITH PARENTS IN THE ORGANIZATION OF PRESCHOOL EDUCATION - Normuradova Dilshoda Alisherovna (Journal of new century innovations, 2022)
Annotation: In this article, there are a number of interruptions in cooperation with parents in preschool education organizations, the opinions of our channel scholars, and general conclusions from foreign systems are highlighted in this article.